Conducting evaluation research with children exposed to violence: How technological innovations in methodologies and data collection may enhance the process. (November 2018) - Wall, Michael A.; Jenney, Angelique; Walsh, Margaret
Abstract: Research and program evaluation processes that engage children and youth are becoming much more common due to influences from children's rights and the acknowledgement that children have the capacity to contribute to research, both as participants and co-researchers (Roberts, 2017). Recent technological advances in the form of tablet and internet-based applications have provided researchers with additional methodological tools to better capture the voices and experiences of children and their caregivers (Livingstone & Blum-Ross, 2017). However, little has been written on the ways in which these new technological advances can improve research experiences for children who have been exposed to intimate partner and family violence, as well as other forms of traumatic experiences. This paper provides a review of current literature and a case study example of how one children's mental health agency has implemented tablet-based data collection procedures.